The impact of environmental management control systems (EMCS) on firm performance: evidence from Malaysian manufacturing companies - Ong, TS (2024)
The business and industrial development has dominantly caused to environmental degradation, necessitating sustainable practices within the manufacturing sector. This study investigates the role of Environmental Management Control Systems (EMCS) in enhancing firm performance across three dimension i.e. economic, environmental, and social. Based on the data from 124 ISO 14001-certified Malaysian manufacturing firms, the study examines both formal and informal EMCS. The findings suggest that formal EMCS with structured rules and standard operating procedures, significantly improve economic and environmental performance. In contrast, informal EMCS which focuses on employee participation and managerial involvement, emphasis on enhancing social performance. These results underline the potential of EMCS as a competitive advantage under the Resource-Based View (RBV) theory, providing actionable insights for firms aiming to align sustainability with profitability. The study shared light on the literature by focusing on the impacts of formal and informal control systems and leading to more effective environmental management strategies in emerging economies.